Risk aversion, entrepreneurial risk, and portfolio selection - Hongyan Fang; John R. Nofsinger (The Journal of Entrepreneurial Finance and Business Ventures, 2009)
Do entrepreneurs consider the risk of their business equity when making investment portfolio allocations? Many people compartmentalize different risks and consider them separately, called mental accounting. Alternatively, the risk substitution hypothesis suggests that entrepreneurs would offset high business income risk by selecting a more conservative investment portfolio. We examine these two hypotheses which have implications for measuring risk tolerance. We find that households with proprietary income show higher risk tolerance than non-entrepreneurs do. Further evidence suggests that a comprehensive measure of relative risk aversion that incorporates households' business income is more reliable and more consistent with their reported risk preference than other measures that do not include business income. In supportive of the risk substitution hypothesis, households do appear to hedge the risk from their private business by decreasing their portion of other risky assets in their investment portfolio.
Keywords: 650